Management of Complex Co-occurring Psychiatric Disorders and High-Risk Behaviors in Adolescence - Welsh, Justine W. (Focus (Am Psychiatr Publ), 2020)
Adolescents often present to treatment with multiple psychiatric diagnoses. The presence of certain co-occurring mental health conditions can significantly affect an individual’s treatment course. Adolescence is also a time of developmentally appropriate risk taking and experimenting with novel behaviors. Difficulties in accurate diagnosis and lack of effective treatment options create obstacles to helping this vulnerable patient population. Appropriate management of adolescents’ complex symptoms and high-risk behaviors during a developmentally sensitive period can be challenging, even for the most skilled of clinicians. This article focuses on the assessment and management of complex, co-occurring psychiatric disorders during adolescence, with specific guidance on how to manage high-risk behaviors, such as self-harm and suicidality. Controversial topics, including antidepressants and youth suicide risk, as well as “off-label” use of mood stabilizers and antipsychotics, are also reviewed.